PERKEMBANGAN JIWA BERAGAMA PADA MASA DEWASA - Mustafa Mustafa (Jurnal Edukasi : Jurnal Bimbingan Konseling, 2016)
It can be said if the adult has the perfect physical growth and reached the psychological maturity to be able to live and contribute together other adults. In American culture, a child is considered not achieve adult status if he has not reached the age of 21 years. Meanwhile in Indonesian culture, a person is considered officially reached adult status if already married, even though he has not yet reached 21 years. psychologists set around the age of 20 years as early adulthood and lasts until around the age of 40-45 years. Adulthood can be said to be the longest period in the life span. During this long period, physical and psychological changes occur at times that can be foreseen that pose adjustment problems, pressures, and expectations. In the teachings of Islam, that the need for religion because man as a creature of God is equipped with a variety of potential (nature) inborn. One such character is the tendency toward religion. One of this nature, that humans accept God as God, in other words, human beings have a tendency is on the origin of religion, because religion is part of his nature. Religious for adults is already a way of living and not just bandwagon. Stability in view of religious life and religious behavior a person, not no longer on the static stability, dynamic stability but, where at one point he knows well the changes. The change occurred because the process of consideration of the mind, knowledge, and perhaps because of the existing conditions.